Pengembangan Media Pembelajaran E-Magazine sebagai Sumber Belajar Biologi Siswa Kelas XII - Fuad, Ainul; Karim, Hilda; Palennari, Muhiddin (Biology Teaching and Learning, 2020)
Abstract. This Research and Development (R and D) concerns on learning media development regarding electronic magazine (e-magazine) for Plant Growth and Development subject. The R and Dâ€™s model used Analyze, Design, Develop, Implement, Evaluate (ADDIE). Validity test obtained from two expert validators and Practicality test obtained from the using of media by teacher and students. The Develop stage of this study conducted by validating e-magazine for further be implemented on SMAN 10 Gowa, Class of XII4 Natural Science. The number of subjects comprised of 29 students. Data collected from interview, observation and questionnaire. The result of validity test showed the average of media feasibility percentage isÂ  82%. While the subject matter feasibility gained 81%. Both of these result showed very decent category which was meant that the media is feasible to be used. The average of teacher and students respond gained 83% and 81 % respectively toward positive respond. From the point of feasibility which had been evaluated by validity and practical test, this study can be conclude that emagazine is valid and practice learning media to be implemented in learning process. Keywords: e-magazine, validity, practicality, plant growth and development